A kind of colorful luminous silk with orthogonal excitation-emission characteristics and preparation method thereof

通过负载双层核壳结构纳米颗粒的桑叶喂食法,制备出在808 nm和980 nm近红外光激发下能够产生多色上转换发光的彩色发光蚕丝,解决了现有发光蚕丝激发波长单一、发光颜色单调的问题,实现了高效的多色发光效果。

CN119014499BActive Publication Date: 2025-03-11INNER MONGOLIA UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411507024.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-03-11
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing preparation methods for luminescent silk have problems such as single excitation wavelength and monotonous luminescent color, which limits its application in the fields of color luminescent textiles, multi-color fluorescence imaging, multi-color coding, etc.

Method used

Using mulberry leaf feeding method loading bilayer core-shell structure nanoparticles with orthogonal excitation-emission characteristics, color luminescent silk that can produce multi-color up-conversion luminescence under near-infrared light excitation under 808 nm and 980 nm is prepared.

Benefits of technology

Multi-color up-conversion luminescence under dual-channel orthogonal excitation is achieved in a single light emitting layer, avoiding the problem of excitation light crosstalk and multi-color luminescence interference, and obtaining an up-conversion luminescence effect with high luminescence intensity and high color purity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119014499B_ABST
    Figure CN119014499B_ABST
Patent Text Reader

Abstract

The present invention discloses a color luminescent silk with orthogonal excitation-emission characteristics and a preparation method thereof, which belongs to the technical field of nano-optical materials, and specifically includes: firstly preparing double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics, performing surface protonation treatment to realize water-soluble modification, and configuring into a nanoparticle aqueous solution, spraying the nanoparticle aqueous solution on mulberry leaves, obtaining mulberry leaves loaded with double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics, feeding five-year-old silkworms until the silkworms are fed to spin silk and form cocoons, and obtaining color luminescent silk with orthogonal excitation-emission characteristics. The color luminescent silk prepared by the method combines two optical frequency up-conversion luminescence mechanisms, and the generated color up-conversion luminescence not only has the advantages of high biological tissue penetration ability, low biological background fluorescence interference, long fluorescence lifetime, high optical stability and narrow-band emission, but also the color luminescent silk can provide multiple luminescent color channels.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano-optical materials, and specifically relates to a colored luminous silk with orthogonal excitation-emission characteristics and a preparation method thereof. Background Art

[0002] Since the Neolithic period, the development of silk in China has a history of more than 5,000 years. At first, as a high-quality textile raw material, silk was widely used in making clothing, textiles and decorations due to its skin-friendly and breathable characteristics. With the in-depth study of silk, researchers have found in recent years that silk also has excellent mechanical properties, biocompatibility and biodegradability. These excellent properties make silk have potential application prospects in the field of bio-optics. For example: silk has good drug encapsulation and controlled drug release functions. Luminescent silk wrapped with nanoluminescent materials carries drugs for photodynamic therapy, and releases drugs by utilizing the biodegradable characteristics of silk. In addition, luminescent silk wrapped with nanoluminescent materials can be used as surgical sutures. By utilizing the biocompatibility and biodegradability of silk, silk does not need to be removed and degrades by itself. The silk protein on the surface of silk basically does not cause inflammatory reactions. The wrapped nanoluminescent materials are used as fluorescent probes to observe surgical healing. In addition, luminescent silk can also be used to make "silk bone nails", silk protein scaffolds and various types of sensors. Therefore, it is of great significance to carry out research on luminescent silk.

[0003] At present, there are three main methods for preparing luminescent silk: genetic engineering, silk post-treatment and feeding method. To a certain extent, genetic engineering will not only artificially disrupt the silkworm gene pool, but also has complex technology and high cost, so it has not been widely used. The silk post-treatment method will destroy the excellent properties of silk itself and even cause the breakage of silk fibers, thus limiting its further application. Compared with the first two methods, the feeding method has the advantages of simple operation, low cost, no secondary pollution, and large-scale production, which has attracted widespread attention from researchers. Although the luminescent silk obtained based on the feeding method shows great application potential in many fields such as biomedicine, the luminescent silk prepared based on luminescent materials (such as organic dyes, carbon quantum dots, upconversion nanoparticles, etc.) is monochromatic under single-wavelength excitation, and there are problems such as single excitation wavelength and monotonous luminescence color, which limits its application in cutting-edge fields such as color luminescent textiles, multi-color fluorescence imaging, multi-color coding, and multi-color sensing. Therefore, the development of a new type of color luminescent silk with orthogonal excitation-emission characteristics is of great value for promoting applications in biomedicine and other fields. Summary of the invention

[0004] In view of the common problems of existing monochromatic luminescent silk, such as single excitation wavelength and monotonous luminescent color, the present invention provides a colored luminescent silk with orthogonal excitation-emission characteristics and a preparation method thereof; the method uses mulberry leaves loaded with double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics to feed fifth-instar silkworms until the silkworms spin silk and make cocoons, thereby obtaining colored luminescent silk; under the excitation of 808 nm near-infrared light, the nanoparticles can produce green upconversion luminescence; under the excitation of 980 nm near-infrared light with different excitation powers, as the excitation light power increases, the nanoparticles can produce dynamic upconversion luminescence color changes from yellow-green to orange, orange-red and then to red, and has broad application potential in cutting-edge fields such as colored luminescent textiles, multi-component bioimaging, and multi-color coding.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing colored luminescent silk with orthogonal excitation-emission characteristics specifically comprises: firstly, using a nanomaterial synthesizer to prepare double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics by a layer-by-layer wrapping method, then using hydrochloric acid to perform surface protonation treatment on the obtained double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics to achieve water-soluble modification, thereby obtaining water-soluble double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics; and configuring the nanoparticles into an aqueous solution with a concentration of 8-12 mg / mL and a pH value of 6-8, then spraying the aqueous solution of the nanoparticles uniformly on fresh and clean mulberry leaves through a sprayer to obtain mulberry leaves loaded with double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics, and finally feeding fifth-instar silkworms with the mulberry leaves loaded with double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics after the mulberry leaves are naturally air-dried until the silkworms spin silk and form cocoons, thereby obtaining colored luminescent silk with orthogonal excitation-emission characteristics.

[0007] Furthermore, the preparation method of the double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics is as follows:

[0008] Firstly, NaYF4:Nd nanoparticles with 808 nm excitation light energy absorption core were prepared, and then used as seeds to induce crystal epitaxial growth of shell layers to form NaYF4:Nd@NaYbF4:Er core-shell structured nanoparticles. Then, the formed core-shell structured nanoparticles were used as seeds to induce epitaxial growth of NaYF4 layers again, finally forming NaYF4:Nd@NaYbF4:Er@NaYF4 double-layer core-shell structured nanoparticles.

[0009] Furthermore, the preparation method of the 808 nm excitation light energy absorption core NaYF4:Nd nanoparticles is as follows:

[0010] A total of 0.4 mmol of YCl3·6H2O and NdCl3·6H2O aqueous solution was added to a mixed solution of 3 mL of oleic acid and 7 mL of octadecene, wherein YCl3·6H2O was 0.32 mmol and NdCl3·6H2O was 0.08 mmol; the resulting mixture was stirred at 150 °C for 60 minutes to remove water and low-boiling point solvent molecules to form an oleic acid complex precursor; then the resulting oleic acid complex precursor was cooled to room temperature, 4 mL of 0.4 mol / L NH4F and 2 mL of 0.5 mol / L NaOH methanol solution were added and the temperature was raised to 50 °C and stirred continuously for 30 minutes; then the temperature was raised to 100 °C and kept under vacuum for 10 minutes to remove methanol, and then the temperature was raised to 290 °C under inert gas protection. °C for 90 minutes; after the reaction, cool to room temperature, separate the core nanoparticles by centrifugal precipitation, wash them repeatedly three times with cyclohexane and ethanol, and finally disperse the products in cyclohexane for further shell growth.

[0011] Furthermore, the preparation method of the NaYF4:Nd@NaYbF4:Er core-shell structure nanoparticles is as follows:

[0012] A total of 0.4 mmol of YbCl3·6H2O and ErCl3·6H2O aqueous solution was added to a mixed solution of 3 mL of oleic acid and 7 mL of octadecene, wherein YbCl3·6H2O was 0.398 mmol and ErCl3·6H2O was 0.002 mmol; the resulting mixture was stirred at 150 °C for 60 minutes to remove water and low-boiling point solvent molecules to form an oleic acid complex precursor; then the resulting mixture was cooled to room temperature, all the prepared NaYF4:Nd core nanoparticles were added, followed by 4 mL of 0.4 mol / L NH4F and 2 mL of 0.5 mol / L NaOH methanol solution, and the temperature was raised to 50 °C and stirred for 30 minutes; then the temperature was raised to 100 °C and then kept under vacuum conditions for 10 minutes to remove methanol, and then heated to 290 °C under inert gas protection for 90 minutes; after the reaction, cooled to room temperature, the core-shell structured nanoparticles were prepared by centrifugal separation and precipitation, and then repeatedly washed three times with cyclohexane and ethanol, and finally the product was dispersed in cyclohexane for further shell growth.

[0013] Furthermore, the preparation method of the NaYF4:Nd@NaYbF4:Er@NaYF4 double-layer core-shell structure nanoparticles is as follows:

[0014] A total of 0.4 mmol of YCl3·6H2O aqueous solution was added to a mixed solution of 3 mL of oleic acid and 7 mL of octadecene, and the resulting mixture was stirred at 150 °C for 60 minutes to remove water and low-boiling point solvent molecules to form an oleic acid complex precursor; then the oleic acid complex precursor was cooled to room temperature, and all the prepared NaYF4:Nd@NaYbF4:Er core-shell structured nanoparticles were added, followed by 4 mL0.4 mol / L NH4F and 2 mL0.5 mol / L NaOH methanol solutions, and the temperature was raised to 50 °C and stirred continuously for 30 minutes; then the temperature was raised to 100 °C and maintained under vacuum conditions for 10 minutes to remove methanol, and then the temperature was raised to 290 °C under inert gas protection for 90 minutes; after the reaction was completed, it was cooled to room temperature, and the double-layer core-shell structured nanoparticles prepared by centrifugal separation and precipitation were then repeatedly washed three times with cyclohexane and ethanol, and finally the product was dispersed in cyclohexane for subsequent water-soluble modification.

[0015] Furthermore, the surface protonation treatment of the obtained double-layer core-shell structured nanoparticles with orthogonal excitation-emission characteristics using hydrochloric acid to achieve water-soluble modification specifically includes:

[0016] The oil-soluble NaYF4:Nd@NaYbF4:Er@NaYF4 double-layer core-shell structured nanoparticles dispersed in cyclohexane were precipitated by centrifugation and dispersed in a mixed solution of anhydrous ethanol and hydrochloric acid in a volume ratio of 1:1. The oleic acid ligands on the surface of the nanoparticles were then removed by centrifugation at 16000 r / min for 20 min. The obtained double-layer core-shell structured nanoparticles with no ligands on the surface were washed twice with ethanol and finally dispersed in deionized water.

[0017] Furthermore, the preparation method of the mulberry leaf loaded with double-layer core-shell structure nanoparticles having orthogonal excitation-emission characteristics specifically comprises:

[0018] First, water-soluble double-layer core-shell structured nanoparticles with orthogonal excitation-emission characteristics are configured into a well-dispersed nanoparticle aqueous solution with a concentration of 8-12 mg / mL and a pH value of 6-8, and then evenly sprayed on fresh and clean mulberry leaves through a sprayer. After the mulberry leaves are naturally air-dried, the air-dried mulberry leaves loaded with double-layer core-shell structured nanoparticles are finally sealed in a sample bag and placed in a refrigerator in the cold storage area at 2-5 °C for future use.

[0019] Furthermore, the method for preparing the colored luminescent silk with orthogonal excitation-emission characteristics specifically comprises:

[0020] After the silkworms enter the fifth instar, mulberry leaves loaded with double-layer core-shell nanoparticles with orthogonal excitation-emission characteristics are fed to the silkworms, so that the nanoparticles on the mulberry leaves enter the silk glands and participate in the production of silk. The silkworms are fed with small amounts and multiple times a day, 5-8 times a day, and 1-3 pieces of mulberry leaves containing nanoparticles are fed each time. The feeding process lasts for 14-16 days until the silkworms spin silk and form cocoons. Finally, the obtained colorful luminescent silk with orthogonal excitation-emission characteristics is dried and sealed for storage.

[0021] Furthermore, the size of NaYF4:Nd core nanoparticles is 22~33 nm, which is used to absorb the energy of 808 nm near-infrared light; the thickness of NaYbF4:Er as the first shell layer is 5~7 nm, which is used to produce green up-conversion luminescence through the energy transfer of Nd→Yb→Er under the excitation of 808 nm near-infrared light; under the excitation of 980 nm near-infrared light with different excitation powers, the energy transfer of Yb→Er produces dynamic color up-conversion luminescence from yellow-green, orange, orange-red to red; the thickness of NaYF4 as the second shell layer is 4~7 nm, which is used to reduce the surface quenching effect.

[0022] Compared with the prior art, the advantages of the present invention are as follows:

[0023] (1) In terms of nanoparticle design and preparation, NaYF4:Nd@NaYbF4:Er@NaYF4 double-layer core-shell structure nanoparticles were prepared by a nanomaterial synthesizer through a layer-by-layer coating method. The size of the nanoparticles was 40-60nm. And by adjusting the composition of the luminescent layer and regulating the energy transfer path (808 nm:Nd→Yb→Er; 980 nm:Yb→Er), in a single luminescent layer (doped with a single Er 3+ The single lanthanide luminescent ion (Er) achieves dual-channel orthogonal excitation upconversion multicolor luminescence. 3+ The orthogonal excitation multicolor luminescence regulation of ions (808 nm: green luminescence; 980 nm: from yellow-green to orange, orange-red to red luminescence) can avoid the problems of excitation light crosstalk, multicolor luminescence mutual interference, harmful energy transfer, etc. caused by co-doping with multiple lanthanide luminescent ions, thereby obtaining upconversion luminescence with high luminescence intensity and high color purity; in the preparation of core-shell structures based on orthogonal two-color or multicolor upconversion luminescence, this double-layer structure is the core-shell structure with the least number of encapsulating shells. Therefore, the preparation method of this double-layer core-shell structure nanoparticle is the simplest method to achieve two-color or multicolor upconversion luminescence under orthogonal excitation.

[0024] (2) In terms of the design and preparation of luminescent silk, the method and principle of combining nanomaterials with silk are fundamentally different from previous research work; traditional luminescent silk is achieved by modifying the surface functional groups of nanomaterials and using the modified functional groups to react with the amino acid side chains of silk to allow the nanomaterials to combine with silk. The present invention, on the other hand, uses dilute hydrochloric acid at pH 4 to protonate the surface of oleic acid-coated double-layer core-shell nanoparticles with orthogonal excitation-emission characteristics, so that the surface ligands fall off in the form of oleic acid molecules, thereby forming positively charged water-soluble nanoparticles without surface ligands, and uses physical electrostatic adsorption to allow the water-soluble nanoparticles to combine with negatively charged silk. The colorful luminescent silk prepared based on the electrostatic adsorption method has the advantages of simple operation, low cost, and excellent luminescence performance.

[0025] (3) In terms of luminescence mechanism, the colorful luminescent silk with orthogonal excitation-emission characteristics prepared by this method combines two optical frequency up-conversion luminescence mechanisms. Under the excitation of 808 nm near-infrared light, green up-conversion luminescence is generated through the energy transfer of Nd→Yb→Er; under the excitation of 980 nm near-infrared light with different excitation powers, the energy transfer of Yb→Er produces dynamic color up-conversion luminescence from yellow-green to orange, orange-red to red. Compared with luminescent silk based on the down-conversion luminescence mechanism (silk coated with organic dyes, carbon quantum dots, etc.), the up-conversion luminescence generated by near-infrared light excitation has the advantages of high biological tissue penetration, low biological background fluorescence interference, long fluorescence lifetime, high optical stability and narrow-band emission, which makes up-conversion luminescent nanoparticles have obvious advantages over organic dyes and carbon quantum dots in silk and biomedical applications. In addition, the two optical frequency up-conversion processes involved in this method based on dual-wavelength near-infrared light excitation of 808 nm and 980 nm are independent and do not interfere with each other, overcoming the problems of single excitation wavelength and monotonous luminescence color under traditional single-wavelength near-infrared light (980 nm) excitation.

[0026] (4) In terms of luminescence performance, the colored luminescent silk with orthogonal excitation-emission characteristics prepared by the present invention can produce green upconversion luminescence under 808 nm near-infrared light irradiation; under 980 nm near-infrared light irradiation with different excitation powers, it can produce dynamic color upconversion luminescence changes from yellow-green to orange, orange-red and then to red. Compared with monochromatic luminescent silk, colored luminescent silk can provide multiple luminescent color channels, making it have broad application potential in cutting-edge fields such as colored luminescent textiles, multi-component bioimaging, and multi-color coding. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following is a brief introduction to the drawings required for the specific embodiments or the description of the prior art. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, the elements or parts are not necessarily drawn according to the actual scale.

[0028] Figure 1 : Schematic diagram of the double-layer core-shell structure NaYF4:Nd@NaYbF4:Er@NaYF4 nanoparticles with orthogonal excitation-emission characteristics;

[0029] Figure 2 :Schematic diagram of the upconversion green light emission mechanism of double-layer core-shell structured nanoparticles with orthogonal excitation-emission characteristics under 808 nm near-infrared light excitation;

[0030] Figure 3 :Schematic diagram of the multicolor upconversion luminescence mechanism of double-layer core-shell structured nanoparticles with orthogonal excitation-emission characteristics under 980 nm near-infrared light excitation at different excitation powers;

[0031] Figure 4 : Transmission electron microscopy (TEM) images and particle size distribution of double-layer core-shell nanoparticles with orthogonal excitation-emission characteristics;

[0032] Among them, ac are transmission electron microscopy (TEM) images of core nanoparticles, core-shell structure nanoparticles, and double-layer core-shell structure nanoparticles, respectively;

[0033] df are the size distribution diagrams of core nanoparticles, core-shell structure nanoparticles and double-layer core-shell structure nanoparticles;

[0034] It can be seen from the figure that the prepared nanoparticles are well dispersed and have uniform morphology. The size range of core nanoparticles is 22~33 nm, the size range of core-shell structure nanoparticles is 35~46 nm, and the size range of double-layer core-shell structure nanoparticles is 35~46 nm.

[0035] Figure 5 : X-ray diffraction pattern of double-layer core-shell structured nanoparticles with orthogonal excitation-emission characteristics;

[0036] It can be seen from the figure that the diffraction peaks of the prepared core nanoparticles, core-shell structure nanoparticles, and double-layer core-shell structure nanoparticles correspond to the standard cards, indicating that the prepared nanoparticles are pure hexagonal phase crystals;

[0037] Figure 6 : EDX spectrum of double-layer core-shell structured nanoparticles with orthogonal excitation-emission characteristics;

[0038] It can be seen from the figure that the elements Na, Y, F, Nd, Yb, and Er are present in the synthesized double-layer core-shell nanoparticles, which is consistent with the feedstock for the preparation of NaYF4:Nd@NaYbF4:Er@NaYF4 nanoparticles;

[0039] Figure 7 : Scanning transmission electron microscopy (STEM) image of double-layer core-shell nanoparticles with orthogonal excitation-emission characteristics; the core-shell structure can be observed from the image;

[0040] Figure 8 : Emission spectra of double-layer core-shell nanoparticles with orthogonal excitation-emission characteristics under 808 nm near-infrared light excitation at different powers;

[0041] It can be seen from the figure that as the excitation power of 808 nm near-infrared light increases, the nanocrystals always maintain green light emission;

[0042] Fig. 9 : Emission spectra of double-layer core-shell nanoparticles with orthogonal excitation-emission characteristics under 980 nm near-infrared light excitation at different powers;

[0043] As can be seen from the figure, with the increase of 980 nm near-infrared light excitation power, the red and green light emission intensities of the nanoparticles will change significantly. Under low 980 nm excitation power, the nanoparticles mainly produce green light emission, and under high 980 nm excitation power, they mainly produce red light emission.

[0044] Fig.10 :Luminescence photos of double-layer core-shell nanoparticles with orthogonal excitation-emission characteristics under near-infrared light excitation at different powers of 808 nm and 980 nm;

[0045] As can be seen from the figure, with the increase of 808 nm near-infrared light excitation power, the nanoparticles always produce green upconversion luminescence; and with the increase of 980 nm near-infrared light excitation power, the nanoparticles can produce dynamic upconversion luminescence color changes from yellow-green to orange, orange-red and then to red;

[0046] Fig.11 :Photos of experimental silkworms under natural light, 808 nm near-infrared light and 980 nm near-infrared light;

[0047] As can be seen from the figure, the experimental silkworm did not emit light under natural light, but produced green and red light under 808 nm near-infrared light and 980 nm near-infrared light respectively. The results showed that the double-layer core-shell structured nanoparticles successfully entered the body of the experimental silkworm.

[0048] Fig.12:Photos of colorful luminescent silk with orthogonal excitation-emission characteristics under natural light, 808 nm near-infrared light, and 980 nm near-infrared light;

[0049] As can be seen from the figure, the obtained silk can produce green and red light under the irradiation of 808 nm near-infrared light and 980 nm near-infrared light, respectively.

[0050] Fig.13 : Colorful luminous silk with orthogonal excitation-emission characteristics is woven into silk clothes, and photos of the silk clothes are obtained under natural light, 808 nm near-infrared light, and 980 nm near-infrared light. DETAILED DESCRIPTION

[0051] The embodiments of the technical solution of the present invention will be described in detail below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention and are therefore only used as examples and cannot be used to limit the protection scope of the present invention.

[0052] It should be noted that, unless otherwise specified, the technical terms or scientific terms used in this application should have the common meanings understood by those skilled in the art to which the present invention belongs.

[0053] Example 1: This example provides a method for preparing double-layer core-shell structured nanoparticles with orthogonal excitation-emission characteristics. The specific preparation process is as follows:

[0054] Preparation of NaYF4:Nd core nanoparticles: Take a 50 mL two-necked round-bottom flask as a reaction vessel, add a total of 0.4 mmol of YCl3·6H2O and NdCl3·6H2O aqueous solution to a mixed solution of 3 mL of oleic acid and 7 mL of octadecene, where YCl3·6H2O is 0.32 mmol and NdCl3·6H2O is 0.08 mmol; stir the resulting mixture at 150 °C for 60 minutes to remove water and low-boiling solvent molecules to form an oleic acid complex precursor. After the resulting mixture is cooled to room temperature, 4 mL of 0.4 mol / L NH4F and 2 mL of 0.5 mol / L NaOH methanol solution are added and heated to 50 °C and stirred continuously for 30 minutes, then heated to 100 °C and kept under vacuum for 10 minutes to remove methanol, and then heated to 290 °C under inert gas protection for 90 minutes. After the reaction is completed, the mixture is cooled to room temperature, and the prepared nanoparticles are precipitated by centrifugation. The nanoparticles are then washed repeatedly with cyclohexane and ethanol several times to obtain NaYF4:Nd core nanoparticles. Finally, the product is dispersed in cyclohexane.

[0055] (2) Preparation of NaYF4:Nd@NaYbF4:Er core-shell structured nanoparticles: A 50 mL two-necked round-bottom flask was used as the reaction container. A total of 0.4 mmol of YbCl3·6H2O and ErCl3·6H2O aqueous solutions were added to a mixed solution of 3 mL of oleic acid and 7 mL of octadecene, where the amount of YbCl3·6H2O was 0.398 mmol and the amount of ErCl3·6H2O was 0.002 mmol. The resulting mixture was stirred at 150 °C for 60 min to remove water and low-boiling point solvent molecules to form an oleic acid complex precursor. After cooling naturally to room temperature, all the core nanoparticles prepared in the first step and 4 mL NH4F (0.4 mol / L) and 2 mL NaOH (0.5 mol / L) methanol solution were added and heated to 50°C and stirred continuously for 30 minutes. Then, the temperature was raised to 100°C and kept under vacuum for 15 minutes to remove methanol, and then the temperature was raised to 290°C under inert gas protection for 90 minutes. After the reaction was completed, it was cooled to room temperature, and the prepared nanoparticles were precipitated by centrifugation, and then washed repeatedly with cyclohexane and ethanol several times to obtain NaYF4:Nd@NaYbF4:Er core-shell structure nanoparticles, and finally the product was dispersed in cyclohexane.

[0056] (3) Preparation of NaYF4:Nd@NaYbF4:Er@NaYF4 double-layer core-shell nanoparticles: A 50 mL two-necked round-bottom flask was used as a reaction vessel. A total of 0.4 mmol of YCl3·6H2O aqueous solution was added to a mixed solution of 3 mL of oleic acid and 7 mL of octadecene. The resulting mixture was stirred at 150°C for 60 minutes to remove water and low-boiling solvent molecules to form an oleic acid complex precursor. After cooling naturally to room temperature, all the core-shell nanoparticles prepared in the second step and 4 mL of 0.4 mol / L NH4F and 2 mL of 0.5 mol / L NaOH in methanol were added thereto and the temperature was raised to 50°C and stirred continuously for 30 minutes. The temperature was then raised to 100°C and kept under vacuum for 15 minutes to remove methanol. The temperature was then raised to 290°C under inert gas protection for 90 minutes. After the reaction is completed, the mixture is cooled to room temperature, and the prepared nanoparticles are precipitated by centrifugation. The nanoparticles are then washed repeatedly with cyclohexane and ethanol several times to obtain NaYF4:Nd@NaYbF4:Er@NaYF4 double-layer core-shell structure nanoparticles. Finally, the product is dispersed in cyclohexane.

[0057] Example 2: This example provides a method for preparing water-soluble double-layer core-shell structured nanoparticles with orthogonal excitation-emission characteristics. The specific preparation process is as follows:

[0058] In order to make the double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics smoothly enter the digestive gland of the experimental silkworm and finally move to the silk gland to participate in the production of silk, the nanoparticles need to be surface modified to make them hydrophilic. In this example, the double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics are water-soluble by surface protonation treatment with hydrochloric acid. The specific steps are: the oil-soluble NaYF4:Nd@NaYbF4:Er@NaYF4 double-layer core-shell structure nanoparticles dispersed in cyclohexane are precipitated by centrifugation, dispersed in a mixed solution of anhydrous ethanol and hydrochloric acid (1 M) with a volume ratio of 1:1, and then centrifuged at 16000 r / min for 20 min to remove the oleic acid ligands on the surface of the nanoparticles. The obtained double-layer core-shell structure nanoparticles without ligands on the surface are washed twice with ethanol and finally dispersed in deionized water.

[0059] Example 3: This example provides a method for preparing mulberry leaves loaded with double-layer core-shell structure nanoparticles having orthogonal excitation-emission characteristics. The specific preparation process is as follows:

[0060] The water-soluble double-layer core-shell structured nanoparticles with orthogonal excitation-emission characteristics prepared in Example 2 are configured into a nanoparticle aqueous solution with a concentration of 8-12 mg / mL and a pH value of 6-8, and then evenly sprayed on fresh and clean mulberry leaves through a sprayer. After the mulberry leaves are naturally air-dried, the air-dried mulberry leaves loaded with the double-layer core-shell structured nanoparticles are finally sealed in a sample bag and placed in a refrigerator in a cold storage area at 2-5°C for storage for later use.

[0061] Example 4: This example provides a method for preparing colored luminescent silk with orthogonal excitation-emission characteristics. The specific preparation process is as follows:

[0062] During the process of silkworms growing from ant silkworms to fourth-instar silkworms, most of the mulberry leaves eaten are used for natural growth of the body and excretion of feces. Only after entering the fifth instar, most of the mulberry leaves eaten will participate in the production of silk. In order not to waste nanoparticles, after the silkworms enter the fifth instar, mulberry leaves loaded with double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics are used to feed the silkworms, so that the nanoparticles on the mulberry leaves enter the silk glands and participate in the production of silk. In order to meet the feeding requirements of silkworms, a small amount of feeding is adopted every day, 5-8 times a day, 1-3 pieces of mulberry leaves containing nanoparticles each time, and the feeding process lasts for 14-16 days until the silkworms spin silk and form cocoons. Finally, the obtained colorful luminescent silk with orthogonal excitation-emission characteristics is dried and sealed for storage.

[0063] The colored luminescent silk with orthogonal excitation-emission characteristics provided by the present invention is obtained by feeding mulberry leaves loaded with double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics to fifth-instar silkworms until the silkworms spin silk and form cocoons. The colored luminescent silk and the double-layer core-shell structure nanoparticles are combined together through the attraction interaction of positive and negative charges, as shown in Table 1; the orthogonal excitation-emission characteristics of the colored luminescent silk benefit from the emission characteristics of the double-layer core-shell structure nanoparticles loaded inside the silk. The double-layer core-shell structured nanoparticles are composed of a 29nm 808nm excitation light energy absorbing core NaYF4:Nd, a 6nm first light-emitting layer NaYbF4:Er, and a 6nm second inert isolation layer NaYF4 from the inside out; the combined action of the three components in the double-layer core-shell structured nanoparticles ultimately achieves multicolor upconversion luminescence under binary orthogonal excitation, that is, green upconversion luminescence is produced through the energy transfer of Nd→Yb→Er under 808nm near-infrared light excitation; and dynamic color upconversion luminescence of yellow-green, orange, orange-red to red is produced through the energy transfer of Yb→Er under 980nm near-infrared light excitation with different excitation powers.

[0064] Table 1 Zeta potential test of the double-layer core-shell nanoparticles and silk surface charge

[0065] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0066] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0067] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing colored luminescent silk with orthogonal excitation-emission characteristics, characterized in that: Specifically include: First, a nanomaterial synthesizer is used to prepare double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics by a layer-by-layer wrapping method, and then hydrochloric acid is used to perform surface protonation treatment on the obtained double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics to achieve water-soluble modification, thereby obtaining water-soluble double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics; and the nanoparticles are prepared into an aqueous solution with a concentration of 8-12 mg / mL and a pH value of 6-8, and then the aqueous solution of the nanoparticles is uniformly sprayed on fresh and clean mulberry leaves by a sprayer to obtain mulberry leaves loaded with double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics, and after the mulberry leaves are naturally air-dried, the mulberry leaves loaded with double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics are finally fed to fifth-instar silkworms until the silkworms are fed to spin silk and form cocoons, thereby obtaining colorful luminous silk with orthogonal excitation-emission characteristics; The method for preparing the double-layer core-shell structured nanoparticles with orthogonal excitation-emission characteristics is as follows: Firstly, NaYF4:Nd nanoparticles with 808nm excitation light energy absorption core were prepared, and then used as seeds to induce epitaxial growth of shell layers to form NaYF4:Nd@NaYbF4:Er core-shell structured nanoparticles. Then, the formed core-shell structured nanoparticles were used as seeds to induce epitaxial growth of NaYF4 layers again, and finally NaYF4:Nd@NaYbF4:Er@NaYF4 double-layer core-shell structured nanoparticles were formed. The method of using hydrochloric acid to perform surface protonation treatment on the obtained double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics to achieve water-soluble modification specifically includes: The oil-soluble NaYF4:Nd@NaYbF4:Er@NaYF4 double-layer core-shell structure nanoparticles dispersed in cyclohexane were precipitated by centrifugation, dispersed in a mixed solution of anhydrous ethanol and hydrochloric acid in a volume ratio of 1:1, and then centrifuged at a speed of 16000r / min for 20min to remove the oleic acid ligands on the surface of the nanoparticles. The obtained double-layer core-shell structure nanoparticles without ligands on the surface were washed twice with ethanol and finally dispersed in deionized water; The size of NaYF4:Nd core nanoparticles is 22-33nm, which is used to absorb the energy of 808nm near-infrared light; the thickness of NaYbF4:Er as the first shell layer is 5-7nm, which is used to produce green up-conversion luminescence through the energy transfer of Nd→Yb→Er under the excitation of 808nm near-infrared light; under the excitation of 980nm near-infrared light with different excitation powers, the energy transfer of Yb→Er produces dynamic color up-conversion luminescence from yellow-green, orange, orange-red to red; the thickness of NaYF4 as the second shell layer is 4-7nm, which is used to reduce the surface quenching effect.

2. A method for preparing colored luminescent silk with orthogonal excitation-emission characteristics as claimed in claim 1, characterized in that: The preparation method of the 808nm excitation light energy absorption core NaYF4:Nd nanoparticles is as follows: A total of 0.4 mmol of YCl3·6H2O and NdCl3·6H2O aqueous solution was added to a mixed solution of 3 mL of oleic acid and 7 mL of octadecene, wherein YCl3·6H2O was 0.32 mmol and NdCl3·6H2O was 0.08 mmol, and the resulting mixture was stirred at 150°C for 60 minutes to remove water and low-boiling point solvent molecules to form an oleic acid complex precursor; then the resulting oleic acid complex precursor was cooled to room temperature, 4 mL of 0.4 mol / L NH4F and 2 mL of 0.5 mol / L NaOH methanol solution were added and the temperature was raised to 50°C and stirred continuously for 30 minutes; then the temperature was raised to 100°C and maintained under vacuum conditions for 10 minutes to remove methanol, and then the temperature was raised to 290°C under inert gas protection for 90 minutes; after the reaction was completed, it was cooled to room temperature, and the core nanoparticles prepared by centrifugal separation and precipitation were then repeatedly washed three times with cyclohexane and ethanol, and finally the product was dispersed in cyclohexane for further shell growth.

3. The method for preparing colored luminescent silk with orthogonal excitation-emission characteristics according to claim 1, characterized in that: The preparation method of the NaYF4:Nd@NaYbF4:Er core-shell structure nanoparticles is as follows: A total of 0.4 mmol of YbCl3·6H2O and ErCl3·6H2O aqueous solution was added to a mixed solution of 3 mL of oleic acid and 7 mL of octadecene, wherein YbCl3·6H2O was 0.398 mmol and ErCl3·6H2O was 0.002 mmol; the resulting mixture was stirred at 150°C for 60 minutes to remove water and low-boiling point solvent molecules to form an oleic acid complex precursor; then the resulting mixture was cooled to room temperature and the prepared NaYF4:Nd core nanoparticles were added, followed by 4 mL of 0.4 0.5 mol / L NH4F and 2 mL 0.5 mol / L NaOH methanol solution were heated to 50°C and stirred continuously for 30 minutes; then the temperature was raised to 100°C and kept under vacuum conditions for 10 minutes to remove methanol, and then the temperature was raised to 290°C under inert gas protection for 90 minutes; after the reaction was completed, it was cooled to room temperature, and the core-shell structured nanoparticles were prepared by centrifugal separation and precipitation, and then repeatedly washed three times with cyclohexane and ethanol, and finally the product was dispersed in cyclohexane for further shell growth.

4. The method for preparing colored luminescent silk with orthogonal excitation-emission characteristics according to claim 1, characterized in that: The preparation method of the NaYF4:Nd@NaYbF4:Er@NaYF4 double-layer core-shell structure nanoparticles is as follows: A total of 0.4 mmol of YCl3·6H2O aqueous solution was added to a mixed solution of 3 mL of oleic acid and 7 mL of octadecene, and the resulting mixture was stirred at 150°C for 60 minutes to remove water and low-boiling point solvent molecules to form an oleic acid complex precursor; then the oleic acid complex precursor was cooled to room temperature, and the prepared NaYF4:Nd@NaYbF4:Er core-shell structured nanoparticles were added, followed by adding 4 mL of 0.4 mol / L NH4F and 2 mL of 0.5 mol / L NaOH methanol solution and heating to 50°C and stirring for 30 minutes; then the temperature was raised to 100°C and maintained under vacuum for 10 minutes to remove methanol, and then the temperature was raised to 290°C under inert gas protection for 90 minutes; after the reaction was completed, it was cooled to room temperature, and the double-layer core-shell structured nanoparticles prepared by centrifugal separation and precipitation were repeatedly washed three times with cyclohexane and ethanol, and finally the product was dispersed in cyclohexane for subsequent water-soluble modification.

5. The method for preparing colored luminescent silk with orthogonal excitation-emission characteristics according to claim 1, characterized in that: The method for preparing mulberry leaves loaded with double-layer core-shell structure nanoparticles having orthogonal excitation-emission characteristics specifically comprises: First, water-soluble double-layer core-shell structured nanoparticles with orthogonal excitation-emission characteristics are configured into a well-dispersed nanoparticle aqueous solution with a concentration of 8-12 mg / mL and a pH value of 6-8, and then evenly sprayed on fresh and clean mulberry leaves through a sprayer. After the mulberry leaves are naturally air-dried, the air-dried mulberry leaves loaded with double-layer core-shell structured nanoparticles are finally sealed in a sample bag and placed in a refrigerator in a cold storage area at 2-5°C for storage.

6. The method for preparing colored luminescent silk with orthogonal excitation-emission characteristics according to claim 1, characterized in that: The method for preparing the colored luminescent silk with orthogonal excitation-emission characteristics specifically comprises: After the silkworms enter the fifth instar, mulberry leaves loaded with double-layer core-shell structure nanoparticles with orthogonal excitation-emission characteristics are used to feed the silkworms, so that the nanoparticles on the mulberry leaves enter the silk glands and participate in the production of silk; the silkworms are fed in small amounts and multiple times a day, 5-8 times a day, with 1-3 pieces of mulberry leaves loaded with nanoparticles each time. The feeding process lasts for 14-16 days until the silkworms spin silk and make cocoons. Finally, the obtained colorful luminescent silk with orthogonal excitation-emission characteristics is dried and sealed for storage.

Citation Information

Patent Citations

  • Mono-doped-enriched core-shell structure up-conversion luminescent material and preparation method thereof

    CN108384547A

  • Preparation method and product of mulberry silk capable of fluorescing under irradiation of near-infrared light

    CN110367209A

  • Encryption material with three-primary-color fluorescence switching characteristic and application of encryption material

    CN111892930A

  • Nano material capable of regulating and controlling orthogonal luminescence characteristic of Ho ions and preparation method of nano material

    CN112779011A